Putting theory into practice: the creation of REALs in the context of today's universities - Sally Ann Kitts; John T. Hancock (Association for Learning Technology, 1999)
Bringing together theory and practice in the context of university teaching is no mean feat. On the one hand, lecturers are challenged and motivated intellectually by the theoretical arguments in the field of education of thinkers such as Grabinger and Dunlap, who have written extensively about comprehensive constructivist learning communities which they term Euch Environments for Active Learning (REALs) (Grabinger and Dunlap, 1995; Grabinger and Dunlap, 1998; Grabinger, Dunlap and Duffield, 1997). Yet, on the other hand, they are also challenged and demotivated on a day-to-day basis with the practicalities of teaching increasing numbers of students with a decreasing unit of resource in institutions where competition for funding is fierce and where there is pressure from external reviews of research and teaching performance.